Penerapan Teknologi Tepat Guna Mesin Pencacah Pada Kelompok Peternak Di Desa Sei Mencirim, Deli Serdang – Sumatera Utara - Hermawan, Indra; Noviandri, Dian; Yolanda, Agnita; Darianto, Darianto; Iswandi, Iswandi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Feed is a vital element crucial to supporting the growth and survival of livestock. Forages, commonly known as livestock fodder, serve as the primary food source for animals and form the foundation of livestock development efforts. Sei Mencirim Village has a livestock farmers' group named "Mencirim Ayu." This group comprises 15 farmers, each raising an average of 10 head of livestock, specifically goats/sheep. The issue faced by the group is the direct feeding of animals due to the lack of a feed chopper. The proposed solution involves creating and providing a livestock feed chopper machine and training on its usage. The outcome of this Community Partnership Program (PKM) activity includes implementing a chopper machine with a capacity of 30-50 kg/hour. Farmers can produce feed more economically for their livestock with this machine, potentially enhancing productivity.